“It’s All about Working with the Story!”: On Movement Direction in Musicals. An Interview with Lucy Hind - George Rodosthenous (Arts, 2020)
Lucy Hind is a South African choreographer and movement director who lives in the UK. Her training was in choreography, mime and physical theatre at Rhodes University, South Africa. After her studies, Hind performed with the celebrated First Physical Theatre Company. In the UK, she has worked as movement director and performer in theatres including the Almeida, Barbican, Bath Theatre Royal, Leeds Playhouse Lowry, Sheffield Crucible, The Old Vic and The Royal Exchange. Lucy is also an associate artist of the award-winning Slung Low theatre company, which specializes in making epic theatre in non-theatre spaces. Here, Lucy talks to George Rodosthenous about her movement direction on the award-winning musical Girl from the North Country (The Old Vic/West End/Toronto and recently seen on Broadway), which was described by New York Times critic Ben Brantley as “superb”. The conversation delves into Lucy’s working methods: the ways she works with actors, the importance of collaborative work and her approach to characterization. Hind believes that her work affects the overall “tone, the atmosphere and the shape of the show”.